The state capital relocation policy and pandemic covid-19: a literature review - Acep Hadinata; Bezoky Cynthia M (Privietlab, 2021)
The National Planning and Development Agency (Bappenas) submitted the findings of a study conducted on the relocation of the Indonesian capital city Jakarta to Kalimantan, a proposal that was made during the era of the first president of the country. The relocation is proposed because of the environmental problems and overcrowding in Jakarta. The inequality in both economic opportunities and development in the satellite communities compared to the city has resulted to urbanization posing pressure on the carrying capacity of the city resulting issues like water scarcity. The capital city relocation is intended to solve these problems, provide more economic growth and also enhance a more efficient governance but it is not priority due the pandemic covid-19.